Fine‐Needle Aspiration for the Evaluation of Hepatic Pharmacokinetics of Vaniprevir: A Randomized Trial in Patients With Hepatitis C Virus Infection. Issue 6 (8th February 2020) - Gao, Wei; Webber, Andrea L.; Maxwell, Jill; Anderson, Melanie; Caro, Luzelena; Chung, Chris; Miltenburg, André M.M.; Popa, Serghei; Van Dyck, Kristien; Wenning, Larissa; Mangin, Eric; Fandozzi, Christine; et al.
Abstract : Fine‐needle aspiration (FNA) for serial hepatic sampling may be an efficient and less invasive alternative to core needle biopsy (CNB), the current standard for liver tissue sampling. In this randomized, open‐label trial in 31 participants with hepatitis C virus genotype 1 infection (NCT01678131/Merck protocol PN048), we evaluated the feasibility of using FNA to obtain human liver tissue samples appropriate for measuring hepatic pharmacokinetics (PK), using vaniprevir as a tool compound. The primary end point was successful retrieval of liver tissue specimens with measurable vaniprevir concentrations at two of three specified FNA time points. Twenty‐nine patients met the primary end point and, therefore, were included in the PK analyses. Hepatic vaniprevir concentrations obtained with FNA were consistent with known vaniprevir PK properties. The shape of liver FNA and CNB concentration‐time profiles were comparable. In conclusion, FNA may be effective for serial tissue sampling to assess hepatic drug exposure in patients with liver disease.